Understanding older Māori informal caregivers’ experiences during the COVID-19 pandemic through Te Whare Tapa Whā - Tyrone Barnard; Shinya Uekusa; Suzanne Phibbs; Steve Matthewman; Christine Stephens; Fiona Alpass; Marcus Tamaira (Kōtuitui, 2025)
Drawing upon Tā Mason Durie’s Te Whare Tapa Whā model, this research explores the impact of the COVID-19 pandemic on the health and wellbeing of older Māori informal caregivers in Aotearoa New Zealand. Utilising information from 35 in-depth interviews conducted with Māori informal/whānau caregivers, this study identifies that the pandemic impacted the physical and mental health of Māori informal caregivers, facing challenges due to lockdown measures, limited access to support services and increased care responsibilities. However, the study predominantly highlights a range of positive aspects of informal caregiving during the pandemic, such as a sense of purpose and fulfilment in their role, enhanced appreciation for loved ones, and increased hononga and whanaungatanga. The study underscores the importance of cultural values and practices in maintaining the wellbeing of Māori informal caregivers and suggests the need for larger social changes to address structural injustices as well as inequalities. Overall, the study provides insights into the experiences of Māori informal caregivers and highlights the significance of recognising and addressing their health and wellbeing during times of crisis.